1999
DOI: 10.1086/302450
|View full text |Cite
|
Sign up to set email alerts
|

A Gene for Inherited Cutaneous Venous Anomalies (“Glomangiomas”) Localizes to Chromosome 1p21-22

Abstract: Venous malformations (VMs) are localized defects of vascular morphogenesis. They can occur in every organ system, most commonly in skin and muscle. They can cause pain and bleeding, and in some critical locations they can be life threatening. Usually venous anomalies occur sporadically, but families with dominant inheritance have been identified. Using linkage analysis, we have established in earlier reports that some families with inherited VMs show linkage to chromosome 9p21; the mutation causes ligand-indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
1
5

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 31 publications
2
106
1
5
Order By: Relevance
“…These findings narrow the locus by 2 cM from AFMA205XD5-D1S236 [Boon, 1999 No 811] to AFMB337XE1-D1S236, a region of about 3 cM (on the basis of the Whitehead/MIT physical map). Comparison of the haplotypes linked to the condition in the 12 families revealed two distinct haplotypes, A and B, shared by seven families (Bl, Bt, Sh, F, T, Bln, Sch), and by four families (Al, Ba, Del, Ad), respectively ( Figure 2).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…These findings narrow the locus by 2 cM from AFMA205XD5-D1S236 [Boon, 1999 No 811] to AFMB337XE1-D1S236, a region of about 3 cM (on the basis of the Whitehead/MIT physical map). Comparison of the haplotypes linked to the condition in the 12 families revealed two distinct haplotypes, A and B, shared by seven families (Bl, Bt, Sh, F, T, Bln, Sch), and by four families (Al, Ba, Del, Ad), respectively ( Figure 2).…”
Section: Resultsmentioning
confidence: 86%
“…5 The number of affected males and females in the 12 families was 35 and 40, respectively, and 59% (26/44) of children of an affected parent had the disorder. Examination of the seven new pedigrees revealed that the condition skipped a generation twice (individuals Del5 and Bln104, Figure 1).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations